2021
DOI: 10.1038/s41433-021-01461-w
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary hyperreflective ovoid mass-like structures (PHOMS) in children

Abstract: Background To analyse structural characteristics and perifoveal/peripapillary vasculature by OCT in children with peripapillary hyperreflective ovoid mass-like structures (PHOMS) and compare the results with those of normal subjects. Methods Forty-five patients (84 eyes) under 18 years old with blurry disc margin were evaluated with spectral domain-OCT and swept course-OCT. Patients were divided into four groups, according to presence of PHOMS and then the size of the existing PHOMS. Eyes with visible optic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 24 publications
2
24
1
Order By: Relevance
“…PHOMS do not correspond to clinically visible ODD. The same OCT findings can also be seen in patients without ODD (16).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…PHOMS do not correspond to clinically visible ODD. The same OCT findings can also be seen in patients without ODD (16).…”
Section: Discussionsupporting
confidence: 72%
“…PHOMS is defined as a hyperreflective ovoid mass-like structure with a hyperreflective interior without sharp outer edges or a hyporeflective core. PHOMS can typically not be found using fluorescence methods, and is not visible on B-scan ultrasonography despite its superficial location ( 16 ). It can also be seen in patients without apparent optic disc edema or poorly demarcated optic discs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 It has been suggested that patients with small diameter of BMO present with larger PHOMS. 21 We did not find a correlation between the diameter of BMO and the volume of PHOMS in patients with either buried or visible ODD. The BMO diameter may therefore not significantly affect the formation and volume of PHOMS.…”
Section: Discussioncontrasting
confidence: 62%
“…We measured the BMO diameter in these latter 14 children and found that 10 of these were in the lowest quartile based on a nested cohort of 130 random subjects measured by Malmqvist et al 15 (see Table 4). A recent study of PHOMS in children 26 found that the BMO in children with PHOMS was significantly smaller than that of controls. Of a total of 45 eyes with PHOMS, 16 eyes had coexisting buried ODD, and there was no report of presence of prelaminar hyperreflective lines.…”
Section: Discussionmentioning
confidence: 89%